The administrative functioning of the Seventh-day Adventist Church in South Africa and the disillusionment and alienation of its members : a catalyst for change - Plaatjes, Calvin William (Stellenbosch : Stellenbosch University, 2011)
Thesis (DTh)--Stellenbosch University, 2007.